ChemInform Abstract: Oxysulfonylation of Alkenes with Sulfonyl Hydrazides under Transition‐Metal‐Free Conditions. Issue 27 (16th June 2016) - Liu, Congrong; Ding, Lianghui; Guo, Guang; Liu, Weiwei
Abstract: affording structurally diverse β‐keto sulfones